Pengaruh Pengalaman Dalam Memoderasi Persepsi Kemudahan Terhadap Intensitas Penggunaan E-Filing - Oktaviani, Rachmawati Meita (ITB AAS INDONESIA, 2020)
The research aims to know the influenced of perceived ease to use and experince as a moderating variable in the taxpayer intensity in to use e-filing as a means of tax reporting. The variables used in this study was the dependent variable is the intensity in using the e-filing and it’s independent variable is perceived ease to use and as well as experince. The data used in the search is the primary data using questionnaries. The number of sample used in this 100 private person that taxpayers have NPWP and use e-filing. This sample collection method was purposive sampling. The data analysis techniquese is multiple linear regression analys. Based on the result of the search showed that perceived ease to use and as well as experince of significant to the intensity of taxpayers in using the e-filing.